Excess mortality in young cancer survivors compared with the general population in Italy: a retrospective study from the Italian population-based cohort of adolescents and young adult cancer survivors - Giorgi Rossi, Paolo; Marinelli, Francesco; Mancuso, Pamela; Mangone, Lucia; Vicentini, Massimo; Bisceglia, Isabella; Bernasconi, Alice; Botta, Laura; Trama, Annalisa; , Ada Working Group (Frontiers in Oncology, 2025)
BackgroundAdolescents and young adults (AYA) cancer survivors experience increased morbidity and mortality from second cancers, cardiovascular, infectious, kidney, and other chronic diseases. We aim to calculate all-causes cancer and non-cancer excess mortality of young cancer survivors compared to the general population.MethodsThe AYA cohort includes cancer patients diagnosed between 1976 and 2013 and alive at 5 years after diagnosis in 30 population-based Cancer Registries and followed up until 31 December 2019. The standardised mortality ratios (SMRs) and absolute excess risks (AERs) per 100,000 for person-years were calculated.Results58,387 5-year survivors were followed up for 427,130 person-years; the median follow-up time was 5.7 years beyond the 5th year after diagnosis. During this time, 4,194 (7.2%) had died by the end of 2019, and only 1.6% were lost to follow-up. Compared with the general population, AYA survivors had higher mortality, overall, the SMR for all-cause mortality was 7.0 (95%CI: 6.8-7.2). The excess of mortality was higher in the first period after diagnosis (5–10 years), SMR 12.8 (95%CI 12.3-13.3), then it decreased, reaching an SMR of 2.2 (95%CI 1.6-3.2) after 30 years.ConclusionsThe excess mortality is mostly due to the malignancy of the primary tumour, but an about 2-fold excess of mortality is also appreciable for non-cancer causes. Young adult cancer survivors face a sevenfold increase in all-cause mortality compared to the general population, with a notable rise in both cancer-related and non-cancer deaths. Thirty years post-diagnosis, the excess risk from cancer and non-cancer causes becomes nearly equal.